Performance Analysis of Flame Retardant 4 Copper Plate Antenna for Lightning Remote Sensing - Periannan D.; Mohamad S.A.; Ahmad M.R.; Esa M.R.M.; Sabri M.H.M.; Seah B.Y.; Lu G.; Yusop N.; Ismail M.M.; Abdul-Malek Z.; Cooray V.; Alkahtani A.A.; et al. (Institute of Physics Publishing, 2023)
Aluminum; Antennas; Climate change; Copper plating; Iron; Lightning; Polytetrafluoroethylenes; Remote sensing; Aluminium plates; Capacitance values; Front-end design; Parallel plates; Performance analysis; Permittivity values; Plate antennas; Remote sensing system; Plate metal